Między ziemią obiecaną a krainą rozczarowań – profile EUROPY we Wszystkich wojnach Lary Wojciecha Jagielskiego - Akram , Sara (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The aim of the article is to point out and describe the profiles of the concept of EUROPE in Wojciech Jagielski’s non-fiction book All Lara’s Wars. Profiling in ethnolinguistics is a process of creating an individual image (profile) of a particular object. The profiles can be diverse, depending on what kind of aspects are important in shaping a particular subjective vision. Based on the linguistic analysis of the chosen quotes from the book, six profiles of EUROPE have been pointed out: promised land, open home, fortress, package, waiting room and land of disappointment. The common aspect which can be found in all the profiles is the geographical one. However, each profile is shaped differently and is dominated by one of the aspects: living, social or civilisational (cultural). Two of the profiles are positively valued (promised land and open home) and the other four are negatively valued, which leads to the conclusion that the image of EUROPE presented in the book is mostly characterised as pejorative.